The Sacralization of the Myth of Prohibition of Leaving the House at Dusk in Sandekala Film: Charles Sanders Pierce’s Semiotic Analysis - Asna Istya Marwantika (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
Abstract Sandekala is a horror film that tells the story of local and religious myths about the prohibition of going out at sunset because the devil hovers around at this time. The combination of myth and religion in this horror film is also an attempt to sacralize myth and religion which is produced in the plot of a scary film scene. This paper aims to determine the position of myth and religious themes in the horror film genre in Indonesia, and discuss how the depiction of the sacred myth comes out at sunset. Sandekala's film was analyzed using Charles Sanders Peirce's semiotic analysis, namely sign, text and interpretant. The results of this paper are first, myth and religion have been used by Indonesian horror film filmmakers since the New Order Era until now. Second, the depiction of the sacredness of the myth of the prohibition of going out at sunset in this film with a dark evening scene, the mother and child as the main characters who have left the house at dusk ignoring the prohibition that has become a myth of society. In addition to confirming the myth of society, this film is also an attempt to remind the segmentation of young people and urbanites who have begun to forget this myth. Abstrak Film Sandekala merupakan film bergenre horor yang bercerita tentang mitos lokal dan religi tentang larangan keluar pada waktu magrib karena setan bergentayangan pada waktu ini. Gabungan antara mitos dan religi dalam film horor ini juga merupakan upaya sakralisasi antara mitos dan religi yang diproduksi dalam alur scene film yang menakutkan. Tulisan ini bertujuan untuk mengetahui posisi tema mitos dan religi dalam genre film horor di Indonesia, dan membahas tentang bagaimana penggambaran sakralisasi mitos keluar pada waktu magrib. Fim Sandekala dianalisis menggunakan analisis semiotik Charles Sanders Peirce yaitu sign, teks dan interpretant. Hasil dari tulisan ini adalah pertama, tema mitos dan religi sudah digunakan sineas film horor Indonesia sejak Era Orde Baru sampai sekarang ini. Kedua, penggambaran sakralisasi mitos larangan keluar magrib di film ini dengan scene suasana magrib yang gelap, ibu dan anak sebagai pemeran utama yang terlanjur keluar rumah waktu magrib ini mengabaikan larangan yang sudah menjadi mitos masyarakat. Film ini selain meneguhkan mitos masyarakat, juga sebagai upaya untuk membidik segmentasi anak muda dan kaum urban yang sudah mulai melupakan mitos ini.